2021
DOI: 10.13057/biodiv/d220344
|View full text |Cite
|
Sign up to set email alerts
|

Cross shelf gradients of scleractinian corals in the Spermonde Islands, South Sulawesi, Indonesia

Abstract: Abstract. Yusuf S, Beger M, Tassakka ACMAR, Brauwer MD, Pricella A, Rahmi, Umar W, Limmon GV, Moore AM, Jompa J. 2021. Cross shelf gradients of scleractinian corals in the Spermonde Islands, South Sulawesi, Indonesia. Biodiversitas 22: 1415-1423. Coral reef ecosystems around the world have suffered extensive degradation, including the reefs of the Wallacea region within the Coral Triangle global biodiversity hotspot. Anthropogenic and natural threats can reduce the level of coral reef biodiversity differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The Spermonde archipelago of Makassar water was chosen as the sampling site because of the biodiversity of the marine invertebrate especially the marine sponge (De Voogd et al 2006). Samalona Island is the middle inner zone of the Spermonde archipelago which is dominated by a healthy coral reef ecosystem (Muller et al 2014;Yusuf et al 2021). The sample of SL.3-SP3 is an encrusting sponge that covers a dead gorgonian.…”
Section: Resultsmentioning
confidence: 99%
“…The Spermonde archipelago of Makassar water was chosen as the sampling site because of the biodiversity of the marine invertebrate especially the marine sponge (De Voogd et al 2006). Samalona Island is the middle inner zone of the Spermonde archipelago which is dominated by a healthy coral reef ecosystem (Muller et al 2014;Yusuf et al 2021). The sample of SL.3-SP3 is an encrusting sponge that covers a dead gorgonian.…”
Section: Resultsmentioning
confidence: 99%
“…(Travaglione et al 2023) and boulder type (Mcleod et al 2019). Yusuf et al (2021) found that coral cover on Spermonde Island ranged from 32.1-33.5%. Meanwhile, research by Parenden et al (2021) found coral cover on Kayangan Island at 4.95%, Samalona Island at 14.08%, and Lae-Lae Island at 9.53% obtained from the coral reef health monitoring report in Makassar City (Sari et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The coral area in the Spermonde Islands is 1,556.97 Ha, which consists of 64 genera from 16 families (Sari et al 2021). Research by Yusuf et al (2021) states that there are as many as 310 species from 62 genera in the Spermonde Islands. Based on monitoring conducted by the Research Center for Oceanography, National Research and Innovation Agency in 2021, coral cover increased in the 2018-2021 time frame by 0.59% and coral diversity in waters near the city of Makassar was lower than in areas far from the mainland of Makassar City.…”
Section: Introductionmentioning
confidence: 99%